A new multiparameter integrated MELD model for prognosis of HBV-related acute-on-chronic liver failure. Issue 34 (August 2016) - Luo, Yue; Xu, Yun; Li, Mingming; Xie, Ya; Gong, Guozhong
Abstract : Abstract: Hepatitis B virus related acute-on-chronic liver failure (HBV-ACLF) is one of the most deadly diseases. Many models have been proposed to evaluate the prognosis of it. However, these models are still controversial. In this study, we aimed to incorporate some characters into model for end-stage liver disease (MELD) to establish a new reliable and feasible model for the prognosis of HBV-ACLF. A total of 530 HBV-ACLF patients who had received antiviral therapy were enrolled into a retrospective study and divided into the training cohort (300) and validation cohort (230). Logistic regression analysis was used to establish a model to predict the 3-month mortality from the patients in the training cohort, and then, the new model was evaluated in the validation cohort. Except for MELD score, 4 other independent factors, namely degree of hepatic encephalopathy (HE), alpha-fetoprotein (AFP), white blood cell (WBC) count, and age, were important for the new model called HBV-ACLF MELD (HAM) model: R = 0.174 × MELD + 1.106 × HE − (0.003 × AFP) + (0.237 × WBC) + (0.103 × Age) − 11.388. The areas under receiver-operating characteristic curve of HAM in the training and validation cohort were 0.894 and 0.868, respectively, which were significantly higher than those of other 7 models. With the best cut-off value of −1.191, HAM achieved higher sensitivity and negative predictive value. We developed a new model that has a great prognostic value of the 3-month mortality of patients with HBV-ACLF. Abstract : Supplemental Digital Content is available in the text